Kedudukan Hukum yang Hidup dalam Masyarakat (Living Law) Perspektif Pasal 2 Undang Undang Nomor 1 Tahun 2023 - Fitriyah Nurrahmah; Berlian Ahsanul Husna (Lembaga Pengembangan Kinerja Dosen, 2026)
The enactment of Law Number 1 of 2023 concerning the Criminal Code (KUHP) has brought a fundamental paradigm reconstruction to the Indonesian criminal justice system through the explicit recognition of the